2014
DOI: 10.1186/1749-799x-9-1
|View full text |Cite
|
Sign up to set email alerts
|

Patients with knee osteoarthritis demonstrate improved gait pattern and reduced pain following a non-invasive biomechanical therapy: a prospective multi-centre study on Singaporean population

Abstract: BackgroundPrevious studies have shown the effect of a unique therapy with a non-invasive biomechanical foot-worn device (AposTherapy) on Caucasian western population suffering from knee osteoarthritis. The purpose of the current study was to evaluate the effect of this therapy on the level of symptoms and gait patterns in a multi-ethnic Singaporean population suffering from knee osteoarthritis.MethodsFifty-eight patients with bilateral medial compartment knee osteoarthritis participated in the study. All patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
48
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 33 publications
6
48
0
1
Order By: Relevance
“…Long-term follow-up would give more insight into the lasting effects of the treatment. However, it reflects previous research on the therapy on different populations with similar improvements in gait and PROM's (33)(34)(35)60). Therefore, it could be assumed that the improvements can be maintained with the high compliance rates in the treatment (32).…”
Section: Discussionsupporting
confidence: 60%
“…Long-term follow-up would give more insight into the lasting effects of the treatment. However, it reflects previous research on the therapy on different populations with similar improvements in gait and PROM's (33)(34)(35)60). Therefore, it could be assumed that the improvements can be maintained with the high compliance rates in the treatment (32).…”
Section: Discussionsupporting
confidence: 60%
“…For example, multiple studies have shown that back pain caused by foraminal stenosis is associated with greater rates of FBSS than pain caused by recurrent disc herniation 811. Entrapment of the superior cluneal nerve is an often overlooked diagnosis in patients presenting with lower back pain with or without leg symptoms 12. Accurate diagnosis is dependent on a thorough history, physical examination, and imaging.…”
Section: Etiologymentioning
confidence: 99%
“…Recent evidence also suggests that there is considerable ability to transfer skills acquired on simulators to the operating room [34]. However, both cadaveric and high technology computerized simulators are limited by availability, expense and resources [8, 9, 11, 19, 20, 35]. Low fidelity simulation allows opportunity to learn and practise basic skills with goal-directed modules; like the incentive to reach training benchmarks to allow trainees to progress [23, 24, 31, 32, 36].…”
Section: Discussionmentioning
confidence: 99%